22 Lessons Learned During COVID-19 Pandemic, a Worldwide Survey: Part 1 -Evolution of Global Neurosurgical Practice. (28th February 2022) - Garg, K.; Deora, H.; Wellington, J.; Tandon, V.; Mishra, S.
Abstract: Aim: During the COVID-19 pandemic, many surveys have analysed the impact of the virus spreading on everyday medical practice, including neurosurgery. However, no one has examined the perceptions of neurosurgeons towards the pandemic, their life changes, and the strategies they implemented to deal with their patients in such a difficult time. Method: From April 2021 to May 2021, a modified Delphi method was used to construct, pilot, and refine the questionnaire. The first part focused on the evolution of global neurosurgical practice during the pandemic. This survey was distributed worldwide among 1000 neurosurgeons. The responses were then collected and critically analysed. Results: Outpatient department practices changed with a rapid rise in teleservices. 63.9% of respondents reported that they had changed their OT practices to emergency cases with occasional elective cases. 40.0% of respondents and 47.9% of their family members reported having suffered from COVID-19 at some time. 56.2% of the respondents reported having felt depressed in the last 1 year. 80.6% of the respondents found online webinars to be a good source of learning. 47.8% of respondents tried to improve their neurosurgical knowledge, while 31.6% spent extra time in research activities during the COVID-19 pandemic. Conclusions: Progressive increase in operative waiting lists, preferential use of telemedicine, reduction in the tendency to complete stoppage of physical clinic services and reduction in the administration and application of PPE kits were evident across the world. Respondents' age impacted how the clinical services and impacted mental health across the global neurosurgical fraternity.